(3YOI GdOGYj hfLGI GdSGYjs - (3GdCSOj, GdMdj, CHh GdYHGS, LeGd GdOjf, CMeO Hf eMeO Hf agO, J (B841(3g`s
(3ChdgG (B:s
(3jLeYIf dG Edg EdG Gddg YOO GdThc hGdTLQ dG Edg EdG Gddg YOO GdTYQ hGdhHQ(B... (3bGd ef bGd Pdc aj cd jhe ef CjGe GdYTQ YTQ eQGJ CYWGg Gddg(B...s
(3BNQgG (B:s
(3eY CfG fLO aj COYjI Cgd GdHjJ Ydjge GdSdGe CdaGXG dG fYQa eYGfjgG hPdc cKjQI aefg CSeGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B1(3, U(B227s
(3GdPQjYI HQbe(B: 1491s
(3GdCYdGe(B: (3L(B1(3, U(B227s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJUha hGdBOGH GdTQYjIs